CARBOHYDRATE METABOLISM ACCORDING TO OBESITY PHENOTYPE - Sekret, Tetiana (Sworld-Us Conference proceedings, 2023)
The article will determine the features of the clinical course, diagnosis of prediabetes and prognosis of the development of diabetes depending on the phenotype of obesity, which will make it possible to further optimize the diagnostic and therapeutic app